Coxiella Endosymbiont of Rhipicephalus microplus Modulates Tick Physiology With a Major Impact in Blood Feeding Capacity - Guizzo, Melina Garcia; Tirloni, Lucas; Gonzalez, Sergio A.; Farber, Marisa D.; Braz, Glória; Parizi, Luís Fernando; Dedavid e Silva, Lucas Andre; da Silva Vaz, Itabajara; Oliveira, Pedro L. (Frontiers in Microbiology, 2022)
In the past decade, metagenomics studies exploring tick microbiota have revealed widespread interactions between bacteria and arthropods, including symbiotic interactions. Functional studies showed that obligate endosymbionts contribute to tick biology, affecting reproductive fitness and molting. Understanding the molecular basis of the interaction between ticks and their mutualist endosymbionts may help to develop control methods based on microbiome manipulation. Previously, we showed that Rhipicephalus microplus larvae with reduced levels of Coxiella endosymbiont of Rhipicephalus microplus (CERM) were arrested at the metanymph life stage (engorged nymph) and did not molt into adults. In this study we performed a transcriptomic differential analysis of the R. microplus metanymph in the presence and absence of its mutualist endosymbiont. The lack of CERM resulted in an altered expression profile of transcripts from several functional categories. Gene products such as DA-P36, protease inhibitors, metalloproteases, and evasins, which are involved in blood feeding capacity, were underexpressed in CERM-free metanymphs. Disregulation in extracellular matrix remodeling was also observed in the absence of the symbiont. Taken together, the observed alterations in gene expression may explain the blockage of development at the metanymph stage and reveal a novel physiological aspect of the symbiont-tick-vertebrate host interaction.